Pengelolaan Pembelajaran Berbasis Proyek melalui Program Bersih Pantai di SDIT Yabis Bontang - Murni, Murni (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
This study explores the management of project-based learning through the beach clean-up program at SDIT Yabis Bontang. The purpose of this research is to describe the planning, implementation, and evaluation, as well as the supporting and inhibiting factors of project-based learning at SDIT Yabis Bontang. This research employs a descriptive qualitative approach using a case study method. Data collection techniques include in-depth interviews, observation, and document analysis. Data analysis follows the Miles and Huberman model, supported by source triangulation and technique triangulation. Data sources consist of three informants: the principal, classroom teachers, and students. After data collection, the information was reduced, presented, and conclusions were drawn. The findings indicate that the planning of project-based learning at SDIT Yabis Bontang involves stages such as socialization, reviewing the guidelines, determining the theme, time, budget, and objectives of the project. Implementation takes place outside the classroom, incorporating local wisdom through a beach clean-up program at Kresik Marangkayu. Evaluation is conducted by classroom teachers in collaboration with parents, while the principal supervises the activities. Supporting factors include strong collaboration with parent associations and financial contributions. Inhibiting factors involve the large number of students and limited bathing facilities, which prolong the activity. Solutions to these challenges include collaborating with parent associations and beach management to provide water and bathing facilities. The study concludes that project-based learning management through the beach clean-up program at SDIT Yabis Bontang is carried out through coordinated planning, implementation, and evaluation involving the principal, teachers, and parents. Obstacles can be addressed in accordance with the structured planning of the project-based learning activity at Kresik Marangkayu Beach.